Losing Much More Than a Transplant: A Qualitative Study of Kidney Transplant Recipients’ Experiences of Graft Failure - Anita Marie Slominska; Elizabeth Anne Kinsella; Saly El-Wazze; Kathleen Gaudio; M. Khaled Shamseddin; Ann Bugeja; Marie-Chantal Fortin; Mireille Farkouh; Amanda Vinson; Julie Ho; Shaifali Sandal (Kidney International Reports)
Introduction: Kidney transplant recipients with graft failure are a growing cohort of patients who experience high morbidity and mortality. Limited evidence guides their care delivery and patient perspective to improve care processes is lacking. We conducted an in-depth exploration of how individuals experience graft failure, and the specific research question was: “What impact does the loss of an allograft have on their lives?” Methods: We adopted an interpretive descriptive methodological design. Semistructured in-depth narrative interviews were conducted with adult recipients who had a history of ≥1 graft failure. Data were collected until data saturation was achieved and analyzed using an inductive and thematic approach. Results: Our study included 23 participants from 6 provinces of Canada. The majority were on dialysis and not waitlisted for retransplantation (60.9%). Our thematic analysis identified that the lives of participants were impacted by a range of tangible and experiential losses that go beyond the loss of the transplant itself. The themes identified include loss of control, loss of coherence, loss of certainty, loss of hope, loss of quality of life, and loss of the transplant team. Although many perceived that graft failure was inevitable, the majority were unprepared. The confusion about eligibility for retransplantation appears to contribute to these experiences. Conclusion: Individuals with graft failure experience complex mental and emotional challenges which may contribute to poor outcomes. The number of patients with graft failure globally is increasing and our findings can help guide practices aimed at supporting and guiding them toward self-management and adaptive coping.